Sustainable Human Resource Management Practices in Achieving Employees’ Sustainable Performance: Evidence in the Hospitality Sector - Chin, Ying Sin; Mohamad, Abang Azlan; Lo, May Chiun (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2023)
Several hospitality businesses face numerous obstacles in enhancing and sustaining employee sustainable performance and commitment due to increased job demands and expectations. This study employs social exchange theory to explore the influence of sustainable HRM practices, such as training and development, employee participation, and employment security practices on employee sustainable performance among executive-level employees in 4- and 5-star hotels. Despite the scarcity of research focusing on the relationship between sustainable HRM practices and employee sustainable performance, especially in the high-end hotel industry, this research analysed 280 valid responses using the PLS-SEM approach. The findings reveal a significant association between training and development and task sustainable performance. Besides, the study identifies a relationship between employee participation and task and relational sustainable performance, while employment security practice appears to have no effect on either task or relational sustainable performance. Although the research primarily targets executives from 4- and 5-star hotels in Malaysia, which may not be representative of other organisational settings, it provides empirical evidence that sustainable HRM practices are directly linked to task and relational sustainable performance, which is beneficial for both researchers and practitioners.